(untitled) (Nusantara Medical Science Journal, 2026)
Introduction: Congenital heart disease (CHD) is one of the most common congenital anomalies and remains a leading cause of neonatal morbidity and mortality worldwide. Early detection through prenatal and postnatal screening plays a crucial role in improving clinical outcomes; however, the diagnostic accuracy of these screening approaches varies across studies. Method: This systematic review was conducted and reported in accordance with the PRISMA 2020 guidelines. A comprehensive literature search was performed in PubMed, Embase, Web of Science, and the Cochrane Library up to December 20, 2025. Title, abstract, and full-text screening were independently conducted by two reviewers, with disagreements resolved through discussion. Eligible studies were English-language articles published between 2015 and 2025 that reported the diagnostic accuracy of prenatal screening (ultrasonography or fetal echocardiography) and/or postnatal screening (pulse oximetry or clinical examination) for CHD detection. Risk of bias and methodological quality were assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool. Due to substantial heterogeneity among studies, data were synthesized narratively. Conclusions: Prenatal and postnatal screening methods exhibit complementary strengths in the detection of CHD. The implementation of an integrated two-stage screening strategy (prenatal–postnatal) is recommended as an optimal approach to enhance early detection and reduce neonatal morbidity and mortality associated with CHD, particularly in low- and middle-income countries.